Diabetes Mellitus and Bacterial Infections: A Review of Main Infections in DM Patients - Yunus, Reni; Wijayati, Fitri; Askrening, Askrening; Rahayu, Dian Yuniar Syanti; Hasan, Fonnie E; Trees, Trees; Fusvita, Angriani (YCAB Publisher, 2024)
Millions of single-celled microscopic organism called bacteria reside within the human body. Numerous infectious diseases in humans are caused by some of these pathogen bacteria. One of the major risk factors for bacterial infections is diabetes mellitus. Bacterial infections and diabetes may have a reciprocal relationship in which some illnesses exacerbate insulin resistance. Diabetes may occur as a result of bacteria in the digestive system. Any organ in a human body can become infected by bacteria. The respiratory tract, gastrointestinal tract, urinary tract, skin, and soft tissues are the most frequently infected areas with diabetes. Uncontrolled hyperglycemia increases the risk of bacterial infections by impairing innate and adaptive immune responses. Furthermore, skin ulceration can result from long-term diabetic consequences such peripheral vascular disease and neuropathy (sensorimotor and autonomic). These conditions can also lead to secondary bacterial infections.